Forms of financing the cultural sector in Poland against the background of solutions from selected European countries - Joanna Posłuszna; Stella Kaczmarek (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The article discusses various forms of financing culture and points to new ways of obtaining funds for artistic creativity in the near future. Culture is an important instrument of each country's policy, it plays a significant role in building the position of a state on the international arena. Although the cultural sector is very important, state budgets contribute only a little to the financing of culture and its functioning depends on various sources of financing. Many entities, belonging to this sector, generate income and co-create the economy. Others have their share in the economic turnover because they participate in the redistribution of goods and provide public artistic and cultural services, in this way creating support for business development and entrepreneurship. The paper highlights different approaches to financing culture in selected European countries, also touching upon America and Canada, and compares them with the situation in Poland.